AN ECONOMIC ANALASIS ON DEMAND OF IRAQI IMPORTS OF CHICKEN MEAT FOR THE PERIOD (1985-2013) - & Al- Badri, Al-Sahoo (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The foreign trade in agricultural products form an important factor for developing countries, including Iraq, because of their great importance in the conduct of agricultural products to regional and global markets and supply there agricultural products from the outside world, thus the imports of agricultural products and goods represent great importance in countries that suffer from the domestic production unable to bridge the consumers needs, especially in the short run.The study aims to analysis and determine the most important economic factors those affecting the quantity of imports of  the chicken meat during the period (1985-2013), where the most important variables those affecting were: the domestic production of chicken meat, the index of domestic price of chicken meat, the index of CIF price of chicken meat and the national income in fixed prices, and these variables were interpreted about (71%) of fluctuations in the imported quantities of the chicken meat, and then constructing model and estimation the demand function of imports of  the chicken meat during the study period, and benefit of parameters of this model in the analysis of economic polices alternatives performance to import the chicken meat, and derive all economic indicators of that function within a period of study and the most important are the elasticites of price and income, as well  as the ability to use the function to forecast the quantity of imports of  the chicken meat in the short run.We have a long-term price elasticity appeared for the import of this article (-1.1611), while the income elasticity of imports appeared (7.5592) and it’s representing the marginal propensity to import and it’s shows that Iraq is price taker, by using Error Correction Model. The study forecasted about the imported quantity of the chicken meat during the period (2015-2025), to using these forecasting in the import policy in the short run.